A SA-Based Wireless Seismic Stress Monitoring System for Concrete Structures - S. Hou; Y. Yu; H. B. Zhang; X. Q. Mao; J. P. Ou (International Journal of Distributed Sensor Networks)
A PZT-based smart aggregate (SA) is capable of full process stress monitoring during earthquakes. A wired seismic monitoring system is prone to failure during earthquakes. Therefore, it is extremely necessary to use the wireless monitoring technique in the SA-based monitoring system. In this paper, the SA is integrated with the ZigBee wireless network which consists of a charge-to-voltage converter, a microprocessing unit, a wireless transmission unit, a base station, and a host computer. The dynamic loading scheme is applied on the SA and the output signal is measured by the wireless system and the wired system in parallel. The performance of the proposed wireless monitoring system is validated by comparing the wired and wireless signals. It is anticipated that this research will demonstrate the potential of using wireless monitoring systems for full damage process monitoring of concrete structures.